Study of amprolium residues in the muscles and organs of broiler in Deir Ezzor Governorate – Syria (Journal of Hama University, 2025)
Abstract: The aim of the study was to conduct a field survey on the extent of the presence of amprolium residues in the muscles and organs of marketed broilers in the governorate of Deir Ezzor. 72 samples were collected from four different areas in the city, divided into 24 samples from each organ or tissue in each area, with six samples for each organ from every region. amprolium residues were extracted from the samples and the remainder was analyzed using high-performance liquid chromatography at a wavelength of 263 nm, a flow rate of 1 ml per minute, and a temperature of 40 degrees Celsius using a C18 type separation column and a mobile length consisting of acetonitrile and phosphate buffer 0.05 M (pH5), Prepared with a mixing ratio of (70/30). The results obtained indicate that there is an intense use of Amprolium in treating coccidiosis, as out of 72 samples collected from four different regions in Deir ez-Zor Governorate, there were 61 samples (84.72%) that showed positive for one residual Amprolium in all samples from the second and third regions. It was positive whether muscle tissue, stomach muscle or liver. The highest concentration of Amprolium residues was in the liver, where the concentration ranged between 62.66 and 933.24 micrograms/kg wet weight. There were 14 liver samples whose concentration of Amprolium residues exceeded the permissible limit according to the European standard. The concentration of amprolium residues in the muscle stomach ranged between 11.07 and 191.96 µg/kg wet weight, including 6 samples in which the concentration of the residues exceeded the permissible limit. In muscle tissue, the concentration ranged between 7.08 and 203.03 micrograms/kg weight, of which only a salt sample was taken, in which the concentration of the residues exceeded the permissible limit according to the European standard.
Keywords: Key words: Amrolium, broiler, residues, muscles, internal organs